Use and effectiveness of neem coated urea: A pan-India exploration - SINGH, A K; KESHAVA, KESHAVA; BURMAN, R ROY; PAUL, SUDIPTA; SOM, SUKANYA; KUMAR, ANJANI; DEKA, B C; TRIPATHI, A K; PRASAD, Y G; SINGH, ATAR; SINGH, RAJBIR; SINGH, LAKHAN; et al. (The Indian Journal of Agricultural Sciences, 2022)
It has become mandatory for all the domestic producers of urea to produce Neem Coated Urea (NCU) since 2015 to reduce overall input cost in farming and to ensure environmental sustainability through enhanced nitrogen use efficiency (NUE). The present study was carried out during 2017–19 with the aim to find out the awareness level of farmers about NCU and its impact on crop productivity. A total of 12,604 farmers across the country were interviewed by 458 Krishi Vigyan Kendras (KVKs). The results of the study showed that 76% farmers were aware about NCU and its effectiveness in increasing crop yield. Farmers of Delhi NCR, Haryana and Rajasthan were found to have the highest awareness while those of Arunachal Pradesh, Sikkim, and Jammu & Kashmir had the lowest level of awareness. Overall, 79% farmers were satisfied with its use. Use of N fertilizers decreased significantly in 2018 compared to 2017 in both the seasons (kharif and rabi), however, the existing rate of application was still significantly higher than recommended doses. The average yield enhancement due to use of NCU was 8.25%. The highest yield increase due to use of NCU was observed in Goa, Madhya Pradesh, and Andaman & Nicobar Islands. Results of the study implied that more emphasis is needed for dissemination of information about NCU through awareness, training and capacity building programmes for farmers and grassroots level extension functionaries.